Plasmonic trapping potentials for cold atoms. (12th June 2018) - Mildner, Matthias; Horrer, Andreas; Fleischer, Monika; Zimmermann, Claus; Slama, Sebastian
Abstract: This paper reports on conceptual and experimental work towards the realization of plasmonic surface traps for cold atoms. The trapping mechanism is based on the combination of a repulsive and an attractive potential generated by evanescent light waves that are plasmonically enhanced. The strength of enhancement can be locally manipulated via the thickness of a metal nanolayer deposited on top of a dielectric substrate. Thus, in principle the trapping geometry can be predefined by the metal layer design. We present simulations of a plasmonic lattice potential using a gold grating with sinusoidally modulated thickness. Experimentally, a first plasmonic test structure is presented and characterized. Furthermore, the surface potential landscape is detected by reflecting ultracold atom clouds from the test structure revealing the influence of both evanescent waves. A parameter range is identified where stable traps can be expected.